Tolerance and behavioral response of juvenile Siganus guttatus to abaca pulp mill effluent - Bradecina, Raul C. (Miagao, Iloilo University of the Philippines in the Visayas, 2003)
Acute bioassay and avoidance-preference tests were done on juvenile S. guttatus using lethal and sublethal concentrations of Abaca pulp mill effluent to assess the fish tolerance and behavioral response to the toxic stress and determine its effect to the chemoreception of biologically important odors. Acute bioassay response data were analyzed by log-probit method. Behavioral response data were calculated from the mean reaction values of the fish samples in the Y-maze apparatus. Results show the fish has a very narrow resistance to the toxic stress of the effluent with LT50 values of 1.6 h for the highest (100%vv-1) and 37 h for the lowest (10%vv-1) concentrations. The 48 h LC50 was located at 9%vv-1 which indicated the fugacity of the effluent and the sensitivity of the fish to its toxicity. The lowest concentration of the effluent with observed significant effect (LOEC) was located at 10%vv-1. The fish showed pronounced and significant discriminating ability at lethal concentration of the effluent. Avoidance reactions of the fish were only observed at 9%vv-1 (lethal/ and 0.9% vv-1 (sublethal) concentrations. The avoidance threshold was found at 0.74% vv-1. Juvenile S. guttatus has a very narrow acuity to the effluent, which was located at a tenth of the mean lethal concentration value. Abaca pulp mill did not mask chemoreception of biologically important odors in juvenile S. guttatus.
Thesis--(M.S. in Ocean Science - Biological Oceanography)--Institute of Marine Fisheries and Oceanology, College of Fisheries and Ocean Sciences, University of the Philippines in the Visayas, April 2003.
Keywords: Abaca pulp; Siganus gutattus